Study on Thermal Comfort and Green Building Index of Neonatal Intensive Care Unit - Chai Chang, Jun; Charlie Sia, Chin Voon; Yeu Yee, Lee; Soon Kok, Heng; Chia Chin, Seng; Annie, Joseph (Semarak Ilmu Publishing, 2025)
The Neonatal Intensive Care Unit (NICU) serves as a vital healthcare facility catering to the needs of premature newborns and infants with critical medical conditions. Given its continuous operation, the NICU demands a substantial energy input. Despite its pivotal role, there exists a notable research gap regarding the most optimal heating, ventilation, and air conditioning (HVAC) systems for these specialized medical environments. This study employs a simulation-based methodology to compare the performance of centralized and split AC systems within NICU settings, considering both fully closed and 90° opened door configurations. Evaluation parameters encompass energy efficiency, thermal comfort attainment, and adherence to green building index (GBI) standards, particularly concerning thermal comfort criteria. Utilizing Autodesk Revit software, an intricate NICU model is constructed, incorporating various elements such as lighting, HVAC infrastructure, occupancy factors, and incubator equipment. Computational Fluid Dynamics (CFD) simulations conducted through Autodesk software facilitate performance assessment, with ensuing GBI ratings providing a metric for comparison. Validation efforts involve scrutinizing airflow characteristics and air velocity against empirical data and prior research findings. Findings reveal that centralized AC systems adeptly ensure uniform cool air distribution, achieving average temperatures of 19.22°C (fully opened door) and 19.18°C (fully closed door). Conversely, split AC systems maintain average temperatures of 23.00°C (fully opened door) and 22.98°C (fully closed door). Projections suggest that centralized systems are poised to fulfill both thermal comfort and air change effectiveness requisites, while split systems may encounter challenges in meeting thermal comfort targets and GBI specifications pertaining to air change efficiency.